Implications of Franciscan Complex graywacke geochemistry for sediment transport, provenance determination, burial‐exposure duration, and fluid exchange with cosubducted metabasites. Issue 5 (17th October 2013) - Ghatak, Arundhuti; Basu, Asish R.; Wakabayashi, John
Abstract [1] Interpretation of graywacke provenance has long been used to evaluate the record of tectonic process in orogenic belts. Our geochemical data from graywackes of the Franciscan subduction complex, California, show that the connection between sedimentary record and geologic processes may be more complex than previously believed. Trace elements and Nd‐Sr‐Pb isotopes of Franciscan graywackes indicate two sources types. One group lacking negative Eu anomaly (Eu/Eu* > 0.9), shows slightly concave‐up heavy rare earth elements, arc‐like trace element patterns, and western Pacific island arc‐like Pb isotopes, reflecting derivation from older accreted oceanic‐arc terranes in the Sierra Nevada‐Klamath Mountains. The other group displays small negative Eu anomalies, with trace element patterns resembling post‐Archean Australian shale and Pb isotopes similar to Jurassic‐Cretaceous Sierran batholith. There is no systematic separation of these two groups by depositional ages. Thus, geochemistry of the graywackes may partly reflect variation in location of sediment delivery systems, rather than solely reflecting evolution of the neighboring arc. Variation of Nd‐Sr isotopes with stratigraphic‐age for the graywackes mimics the trends of the coeval Great Valley Group clastic‐rocks, suggesting that (1) they share the same sediment sources, (2) there are no "exotic" sediment sources that fed the Franciscan trench, and (3) burial‐exposure cycles for Franciscan clastic rocks were comparatively brief. Comparison of Franciscan graywacke and metabasite geochemistry corroborates earlier conclusions that metabasites had little or no chemical exchange with fluids from cosubducted graywacke. Detrital zircon age populations, major element chemistry, and detrital framework modes, when compared to our data suggest that the former three parameters underrepresent the mafic component of clastic sediment provenance.